Modern Art Interactive Design Relying on Neural Network Intelligent Algorithms - Yanan Guo (Advances in Multimedia)
The extraction speed of current art exchange element is relatively low, and its effect is relatively poor, so is the effect of art exchange. Therefore, a new art exchange method has been developed with respect to artificial intelligence technology, which analyzes the background of current art, providing a good environment foundation for the exchange place to integrate the artificial intelligence technology after the exchange, and interacts with the network artificial intelligence technology and the multimedia multielement exchange art in the control. It has been proved through practice that artificial intelligence technology embodies the advantages of design tools and the improvement of efficiency in modern art exchange; it allows the current diversity of artistic interaction and enables it to obtain new development in the current new technological background.